2006
DOI: 10.1038/sj.npp.1301140
|View full text |Cite
|
Sign up to set email alerts
|

β1 Adrenergic Receptors in the Bed Nucleus of Stria Terminalis Mediate Differential Responses to Opiate Withdrawal

Abstract: The negative physical and affective aspects of opioid abstinence contribute to the prolongation of substance abuse. Withdrawal treatment is successful only in a subset of subjects, yet little is known about the neurobiological causes of these individual differences. Here, we compare the somatic and motivational components of opioid withdrawal in animals with high reactivity (HR) vs low reactivity (LR) to novelty, a phenotype associated with differential vulnerability to drug abuse. During withdrawal, HR relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 58 publications
3
19
0
2
Order By: Relevance
“…Of particular interest are findings from Delfs et al (2000) who found that intra-BNST infusions of a noradrenergic β1/β2 receptor antagonist cocktail (betaxolol + ICI 118,551), or of the non-selective β-receptor antagonist S -propranolol, or of the noradrenergic α2 agonist clonidine (which inhibits norepinephrine release via actions on presynaptic receptors (Forray et al , 1995; Forray et al , 1997) each block the development of withdrawal-induced place aversions with only modest (e.g., teeth chattering, eye twitching) or non-existent (e.g., wet dog shakes, jump escapes) effects on the acute somatic signs of withdrawal. Similar results have been reported by Cecchi et al (2007). The noradrenergic system was targeted in these studies because of the extraordinarily high levels of norepinephrine found in the BNST (e.g., Brownstein et al , 1974; Kilts and Anderson, 1986) and released during stress (Pacak et al , 1995; Pardon et al , 2002).…”
Section: Does Bnst Plasticity Mediate Stress-induced Anxiety?supporting
confidence: 78%
“…Of particular interest are findings from Delfs et al (2000) who found that intra-BNST infusions of a noradrenergic β1/β2 receptor antagonist cocktail (betaxolol + ICI 118,551), or of the non-selective β-receptor antagonist S -propranolol, or of the noradrenergic α2 agonist clonidine (which inhibits norepinephrine release via actions on presynaptic receptors (Forray et al , 1995; Forray et al , 1997) each block the development of withdrawal-induced place aversions with only modest (e.g., teeth chattering, eye twitching) or non-existent (e.g., wet dog shakes, jump escapes) effects on the acute somatic signs of withdrawal. Similar results have been reported by Cecchi et al (2007). The noradrenergic system was targeted in these studies because of the extraordinarily high levels of norepinephrine found in the BNST (e.g., Brownstein et al , 1974; Kilts and Anderson, 1986) and released during stress (Pacak et al , 1995; Pardon et al , 2002).…”
Section: Does Bnst Plasticity Mediate Stress-induced Anxiety?supporting
confidence: 78%
“…The BNST has one of the highest concentrations of norepinephrine in the brain, and opiate withdrawal activates BNST-projecting cells in the A1 and A2 noradrenergic cell groups of the caudal medulla. Lesions of the ventral noradrenergic bundle, which interrupt the projection of these cell groups to the BNST, reduce opiate-withdrawal-induced place aversion, as do injections of b-adrenergic-receptor antagonists into the BNST itself, even though these same manipulations have little effect on the somatic symptoms of withdrawal (Aston-Jones et al 1999;Delfs et al 2000; and see also Cecchi et al 2007).…”
Section: Role Of the Cea And Bnst In Drug Withdrawalmentioning
confidence: 96%
“…Blocking both β 1 -AR and β 2 -ARs abolishes withdrawal-induced place aversion (Aston-Jones et al, 1999). A selective β 1 -AR antagonist in the dBNST blocks withdrawal-induced aversion and attenuates opiate-withdrawal symptoms in rats with high reactivity to novelty (Cecchi et al, 2007).…”
Section: Norepinephrinementioning
confidence: 99%